Pengaruh Harga Diskon Dan Persepsi Produk Terhadap Nilai Belanja Serta Perilaku Konsumen - Sadana Devica (BIP's JURNAL BISNIS PERSPEKTIF, 2015)
This study aims to determine the effect of price discounts and product perception of the value of shopping and buying behavior of consumers to the category of fashion products. The research was carried out in a department store located in the shopping center Tunjungan Plaza Surabaya. A total of 100 respondents were volunteers in this study, while the limits studied fashion product categories include apparel, handbags, footwear (shoes, slippers and sandals), as well as accessories (glasses, jewelery and hats). The results of this study indicate that the price discount hedonic effect on consumer spending. Similarly, the product may increase the perception variable hedonic shopping. Furthermore a positive effect was also shown in the variable perception of consumer products for the shopping utilitarian, hedonic and utilitarian shopping and have a positive influence on consumer buying behavior in a department store.